2017
DOI: 10.1177/1947603517713816
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Study Comparing Microfracture and Local Adherent Transplantation of Autologous Adipose-Derived Stem Cells Followed by Intraarticular Injection of Platelet-Rich Plasma for the Treatment of Chondral Defects in Rabbits

Abstract: Objective This study aimed to compare microfracture and application of adipose-derived stem cells (ADSCs) by local adherent technique enhanced by platelet-rich plasma (PRP) to provide a new approach for the repair of cartilage defect. Design Full-thickness cylindrical defects were created in the medial femoral condyle in 9 New Zealand White rabbits (5 months old, 4.65 ± 0.20 kg). Two groups of rabbits ( n = 3) were either treated with ADSCs (Group 1) or the microfracture technique (Group 2) following intraarti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Mesenchymal stem cells loaded on Tantalum have been shown to improve cartilage repair in a large osteochondral defect model in goat [36]. Adipose stem cells in combination with different scaffold have been shown to ameliorate cartilage regeneration in a different animal models [3739]. Adipose stem cells have been tested in phase II clinical trial for knee osteoarthritis treatment, and the results have indicated the improvement of joint function, pain, quality of life, and cartilage regeneration [40].…”
Section: Discussionmentioning
confidence: 99%
“…Mesenchymal stem cells loaded on Tantalum have been shown to improve cartilage repair in a large osteochondral defect model in goat [36]. Adipose stem cells in combination with different scaffold have been shown to ameliorate cartilage regeneration in a different animal models [3739]. Adipose stem cells have been tested in phase II clinical trial for knee osteoarthritis treatment, and the results have indicated the improvement of joint function, pain, quality of life, and cartilage regeneration [40].…”
Section: Discussionmentioning
confidence: 99%
“…Although repair responses induced by BMS along with characterization of BMSCs has been investigated in animal models before, 13-16 this is the first study designed to correlate the early repair response with biological properties of BMSCs from the same location to elucidate the mechanism of location-dependent and interanimal variation observed in cartilage repair. We chose a rabbit model since comparison of the structure of subchondral bone—the primary source of repair in marrow stimulation—has revealed striking similarities between human condyles and rabbit trochlea, making this a relevant preclinical model.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of orthopaedics, a series of previous studies on PRP treatment revealed its positive effect in patients with osteoarthritis compared with hyaluronic acid injection and placebo [ 65 ]. Various in vitro [ 66 , 67 , 68 ] and animal studies [ 69 , 70 , 71 , 72 ] also used PRP to demonstrate the beneficial effect of PRP on cell proliferation, structural modulation and inflammation status in the knee joint.…”
Section: Platelet-rich Plasmamentioning
confidence: 99%